2010
DOI: 10.1364/ao.49.004217
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Rayleigh–Brillouin scattering of ultraviolet light in nitrogen, dry air, and moist air

Abstract: Atmospheric lidar techniques for the measurement of wind, temperature, and optical properties of aerosols rely on the exact knowledge of the spectral line shape of the scattered laser light on molecules. We report on spontaneous Rayleigh-Brillouin scattering measurements in the ultraviolet at a scattering angle of 90 degrees on N(2) and on dry and moist air. The measured line shapes are compared to the Tenti S6 model, which is shown to describe the scattering line shapes in air at atmospheric pressures with sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 45 publications
(66 reference statements)
5
57
0
Order By: Relevance
“…W hile such an approach may work, it is not internally consistent because the effective kinetic param eters are not w ell defined, and an agreem ent betw een m odel and experim ent m ust b e deem ed fortuitous. Still, in a separate study on spontaneous Rayleigh-B rillouin scattering on dry and m oist air, m easured spectra could be w ell-represented by the Tenti S6 model, taking the effective transport coefficients of air as param eters [32] .…”
Section: Mixtures O F Gasesmentioning
confidence: 99%
“…W hile such an approach may work, it is not internally consistent because the effective kinetic param eters are not w ell defined, and an agreem ent betw een m odel and experim ent m ust b e deem ed fortuitous. Still, in a separate study on spontaneous Rayleigh-B rillouin scattering on dry and m oist air, m easured spectra could be w ell-represented by the Tenti S6 model, taking the effective transport coefficients of air as param eters [32] .…”
Section: Mixtures O F Gasesmentioning
confidence: 99%
“…11,12 The calculated S6 curves are convolved with the measured instrument function of width 232 MHz; the fact that the series of overlapping RB-profiles measured by the FPI never reaches the zero level is accounted for (see also Ref. 11).…”
Section: A Data Processing Proceduresmentioning
confidence: 99%
“…In particular, in recent studies, the 6-component version of the Tenti-model 10 (Tenti S6) was found to accurately describe the RB-scattering profile in various atomic and molecular gases 11 and in air. 12 The RB-scattering profile can be measured by different means. The direct method analyzes the scattered light via a Fabry-Perot interferometer, as was pursued in the early studies.…”
Section: Introductionmentioning
confidence: 99%
“…In 1974, Tenti et al [6] developed a modelthe so-called Tenti S6 model -for describing RB spectra of light scattered in molecular gases of single species, which is since then considered as the best model available. Recently performed laboratory studies [7][8] into account the mixed nature of air as scattering medium. In order to retrieve temperature from measured RB profiles, they have to be analyzed with the Tenti S6 model in a certain optimization procedure as for instance a least-squares fit with temperature as free fitting parameter.…”
Section: Introductionmentioning
confidence: 99%